1998
DOI: 10.1200/jco.1998.16.9.3044
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's tumors with primary lung metastases: survival analysis of 114 (European Intergroup) Cooperative Ewing's Sarcoma Studies patients.

Abstract: Chemotherapy response of the primary tumor is a prognostic factor in patients with ET with ppm. Strategies of treatment intensification warrant further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
3
10

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(132 citation statements)
references
References 23 publications
8
111
3
10
Order By: Relevance
“…The regimens that were applied are listed in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] High-dose chemotherapy (HDC) with hematopoietic stem cell rescue was received by 51 patients, including 48 patients who received autologous peripheral blood stem cell transfusion (PBSCT) and 3 patients who underwent autologous bone marrow transplantation.…”
Section: Treatmentmentioning
confidence: 99%
“…The regimens that were applied are listed in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] High-dose chemotherapy (HDC) with hematopoietic stem cell rescue was received by 51 patients, including 48 patients who received autologous peripheral blood stem cell transfusion (PBSCT) and 3 patients who underwent autologous bone marrow transplantation.…”
Section: Treatmentmentioning
confidence: 99%
“…[1][2][3][4] However, patients with bulky primary tumors, with multifocal or metastatic disease at presentation or with refractory or recurrent disease have a very poor prognosis, with only 10-30% survival rate at 3 years. [1][2][3][4] As some studies have shown that there is a positive linear relationship between the dose of cytoreductive agents and tumor response, 5 the approach of high-dose chemo-and/or radiation therapy followed by autologous hematopoietic SCT (HSCT) has been used in the practice of treatment of EFT in an attempt to improve the disease outcome and overall survival (OS) rate. We report our experience with further intensification of treatment in children and adolescents with high-risk EFT.…”
Section: Introductionmentioning
confidence: 99%
“…[67] Tüm akciğer radyoterapisi (Whole lung irradiation -WLI), sadece akciğerde metastazı olan hastalarda sağkalımı arttırır. [68] …”
Section: Lokalize Hastalıkta Tedavi Ve Radyoterapinin Yeriunclassified